KOMUNIKASI INTERPERSONAL DALAM MENINGKATKAN KEPUASAN PEMUSTAKA DI UPT PERPUSTAKAAN UIN IMAM BONJOL PADANG - Putri, Fionna Salsabila (Jurnal Al- Ma'arif : Ilmu Perpustakaan dan Informasi Islam, 2024)
The purpose of this study is to investigate how the interpersonal communication of librarians at the UPT Library UIN Imam Bonjol Padang contributes to higher user satisfaction. In addition to providing resources, the library serves as an academic information center by fostering human connections between librarians and patrons. Descriptive qualitative research methodology is employed, and data is gathered via literature reviews, interviews, documentation, and observation. The findings demonstrated that library satisfaction is positively impacted by effective interpersonal communication. Effective interpersonal communicators are able to comprehend user requirements, respond to those needs, and provide a welcoming environment for patrons.